Software Engineering meets Artificial Intelligence - Klus, Holger; Knieke, Christoph; Rausch, Andreas; Wittek, Stefan (Electronic Communications of the EASST, 2023)
With the increasing use of AI in classic software systems, two worlds are coming closer and closer to each other that were previously rather alien to each other, namely the established discipline of software engineering and the world of AI. On the one hand, there are the data scientists, who try to extract as many insights as possible from the data using various tools, a lot of freedom and creativity. On the other hand, the software engineers, who have learned over years and decades to deliver the highest quality software possible and to manage release statuses. When developing software systems that include AI components, these worlds collide. This article shows which aspects come into play here, which problems can occur, and how solutions to these problems might look like. Beyond that, software engineering itself can benefit from the use of AI methods. Thus, we will also look at the emerging research area AI for software engineering.